The Effect of Quality of Work Life and Job Satisfaction on Performance with Knowledge Sharing as Mediate Variable of Private Universities Lecturers’ During Pandemic Covid-19 - Daniel Ong Kim Kui; Yohana F. Cahya Palupi Meilani; Innocentius Bernarto (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of quality of work life and job satisfaction on the performance of lecturers at private universities in Tangerang with mediated by knowledge sharing. This study used 120 respondents. Data were collected through a questionnaire using a Likert scale of 1-5 and obtained using google form with convenience sampling. The data processing in this study uses the Smart PLS application, where the results show that the quality of work life does not significantly effect to performance of lecturers. Job satisfaction significantly effect to performance of lecturers. The knowledge sharing significantly effect to the performance of lecturers. Knowledge sharing can mediate effect of quality of work life on the performance of lecturers. While knowledge sharing does not able to mediate effect of job satisfaction on the performance of lecturers.